Let A : = 8 − 8 − 8 + 8 − 8 − 8 + ⋯ B : = 3 9 + 9 3 9 + 9 3 9 + 9 3 9 + 9 3 9 + ⋯ Find B − A .
Details and assumptions:
The sign pattern in the first radical is ( − − + ) .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
Is there any other method to solve the problem?
1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 |
|
Problem Loading...
Note Loading...
Set Loading...
Let A = 8 − b , b = 8 − c and c = 8 + A . Then A 2 = 8 − b , b 2 = 8 − c and c 2 = 8 + A . Let A = − a , then we have the following system: a 2 b 2 c 2 = 8 − b = 8 − c = 8 − a ⋯ ( 1 ) ⋯ ( 2 ) ⋯ ( 3 ) Let m = a + b + c , n = a b + b c + c a and p = a b c . Sum (1), (2) and (3) to obtain: a 2 + b 2 + c 2 m 2 − 2 n n = 2 4 − ( a + b + c ) = 2 4 − m = 2 1 m 2 + 2 1 m − 1 2 ⋯ ( 4 ) Subtract (1)-(2), (2)-(3) and (3)-(1): a 2 − b 2 b 2 − c 2 c 2 − a 2 = − ( b − c ) = − ( c − a ) = − ( a − b ) ⟹ ( a + b ) ( a − b ) ⟹ ( b + c ) ( b − c ) ⟹ ( c + a ) ( c − a ) = − ( b − c ) = − ( c − a ) = − ( a − b ) ⋯ ( 5 ) ⋯ ( 6 ) ⋯ ( 7 ) Multiply (5), (6) and (7), and remember that a , b and c are all distinct: ( a + b ) ( a − b ) ( b + c ) ( b − c ) ( c + a ) ( c − a ) ( a + b ) ( b + c ) ( c + a ) m n − p p = − ( a − b ) ( b − c ) ( c − a ) = − 1 = − 1 = m n + 1 ⋯ ( 8 ) We also have, using (1), (2) and (3): b ( 8 − b 2 ) = ( 8 − a 2 ) c c ( 8 − c 2 ) = ( 8 − b 2 ) a a ( 8 − a 2 ) = ( 8 − c 2 ) b ⟹ 8 b − b 3 = 8 c − c a 2 ⟹ 8 c − c 3 = 8 a − a b 2 ⟹ 8 a − a 3 = 8 b − b c 2 ⋯ ( 9 ) ⋯ ( 1 0 ) ⋯ ( 1 1 ) Sum (9), (10) and (11): a 3 + b 3 + c 3 m 3 − 3 m n + 3 p = a b 2 + b c 2 + c a 2 = a b 2 + b c 2 + c a 2 ⋯ ( 1 2 ) Multiply (1) by c , (2) by a and (3) by b : b c c a a b = 8 c − c a 2 = 8 a − a b 2 = 8 b − b c 2 ⋯ ( 1 3 ) ⋯ ( 1 4 ) ⋯ ( 1 5 ) Sum (13), (14) and (15): a b + b c + c a a b 2 + b c 2 + c a 2 = 8 ( a + b + c ) − ( a b 2 + b c 2 + c a 2 ) = 8 m − n ⋯ ( 1 6 ) Equate (12) and (16): m 3 − 3 m n + 3 p = 8 m − n ⋯ ( 1 7 ) Substitute (8) in (17): m 3 − 3 m n + 3 ( m n + 1 ) m 3 + 3 = 8 m − n = 8 m − n ⋯ ( 1 8 ) Substitute (4) in (18): m 3 + 3 m 3 + 2 1 m 2 − 2 1 5 m − 9 ( m − 3 ) ( m + 2 ) ( m + 2 3 ) = 8 m − ( 2 1 m 2 + 2 1 m − 1 2 ) = 0 = 0 ⋯ ( 1 9 ) From (19), (4) and (8) we obtain the solutions ( m , n , p ) = ( 3 , − 6 , − 1 7 ) , ( m , n , p ) = ( − 2 , − 1 1 , 2 3 ) and ( m , n , p ) = ( − 2 3 , − 8 9 3 , 1 6 2 9 5 ) . Since a < 0 and b , c > 0 , then p = a b c < 0 , so the only solution is ( m , n , p ) = ( 3 , − 6 , − 1 7 ) .
Let P ( z ) have roots a , b , c . Then P ( z ) = z 3 − 3 z 2 − 6 z + 1 7 , so we have to solve z 3 − 3 z 2 − 6 z + 1 7 = 0 . Let z = z ′ + 1 , then the equation becomes z ′ 3 − 9 z ′ + 9 = 0 . Since a = − A we have ( − A − 1 ) 3 − 9 ( − A − 1 ) + 9 = 0 ⋯ ( 2 0 )
To find B notice that B = 3 9 + 9 B , then: B 3 − 9 B − 9 = 0 ⋯ ( 2 1 ) Sum (20) and (21): ( − A − 1 ) 3 + B 3 − 9 ( − A + B − 1 ) ( − A + B − 1 ) ( ( − A − 1 ) 2 − ( − A − 1 ) B + B 2 ) − 9 ( − A + B − 1 ) ( − A + B − 1 ) ( A 2 + 2 A + 1 + A B + B + B 2 − 9 ) = 0 = 0 = 0 Since the second factor cannot be zero (left as an exercise), we must have − A + B − 1 = 0 , or B − A = 1 .